Assessing conservation priorities of xenarthrans in Argentina - Tognelli, Marcelo F. (2011)
In this study, we combine species distribution models with a reserve selection approach to assess the degree of representation of xenarthrans in the existing protected area network of Argentina, and to identify conservation priority areas that may help expand the current system. Species distribution models were developed from species’ occurrence records using a maximum entropy algorithm. Maps of species distributions were produced for 15 of the 16 species currently present in the country. To assess the performance of the existing protected area network in representing all modeled species, and to identify priority areas to expand the current reserve system, we used the software Zonation. Overall, all species modeled are represented in the existing protected area network. However, the percentage of their ranges covered by protected areas is very low (average = 6.7%; range = 1.7–17.6%). To represent at least 5% of the distribution of each species, 8.8% of the country’s area would be needed, and species with restricted ranges have the greatest increase in representation in this scenario. When 10% of the country is set aside for conservation, species representation increases considerably, again favoring range-restricted species. Most of the areas identified as conservation priorities are under strong anthropogenic pressures, including deforestation, agricultural expansion, and hunting. Our analysis provides a preliminary assessment of conservation priorities for the xenarthrans of Argentina, and we hope will serve as guideline to focus future conservation assessments at more refined scales.